The 'Pritchard Trap': A novel quantitative survey method for crayfish. Issue 2 (7th June 2021) - Pritchard, Eleri G.; Chadwick, Daniel D. A.; Patmore, Ian R.; Chadwick, Michael A.; Bradley, Paul; Sayer, Carl D.; Axmacher, Jan C.
Abstract: As crayfish invasions continue to threaten native freshwater biota, a detailed understanding of crayfish distribution and population structure becomes imperative. Nonetheless, most current survey methods provide inadequate demographic data. The quantitative 'Triple Drawdown' (TDD) dewatering method has highlighted the importance of such data, yet practical constraints prevent its large‐scale application. Here, we introduce the 'Pritchard Trap', a novel passive sampling method that reliably generates quantitative crayfish population data while requiring substantially lower sampling effort than TDDs. This quadrat‐style sampler was extensively tested in headwater streams of North Yorkshire, England, along an invasion gradient for signal crayfish ( Pacifastacus leniusculus ) from well‐established sites to mixed populations of signal crayfish and native white‐clawed crayfish ( Austropotamobius pallipes ). The Pritchard Trap was trialled over several time intervals to determine the minimum required trap deployment time. TDDs at the same sites allowed for a robust evaluation of Pritchard Trap sampling accuracy in representing crayfish densities and population structure. The Pritchard Trap successfully sampled both invasive and native crayfish (8–42 mm carapace length). A minimum passive deployment time of 4 days was required. At low crayfish densities (0.5 individuals m −2 ), increased trapping effort was necessary to achieve accurate population density and size class distribution estimates. The Pritchard Trap required substantially less sampling effort (working hours) and resources than the TDD, whilst also posing less risk to non‐target species. The Pritchard Trap, for the first time, affords logistically simple, truly quantitative investigations of crayfish population demographics for headwater systems. It could be integrated into crayfish research and management, for example to explore density‐dependent ecological impacts of invasive crayfish and their management responses or to monitor populations and recruitment in native crayfish conservation initiatives. Abstract : The 'Pritchard Trap' (PT) is a novel passive survey method for crayfish, that was tested in rocky headwaters in Northern England. PTs are filled with naturally occurring substrate and deployed for a minimum of four days. The PTs reliably generated quantitative crayfish population data, including density and size structure, along an invasion gradient from well‐established invasive signal crayfish populations to mixed populations of signal crayfish and native white‐clawed crayfish.